Produção científica em Sociologia da Educação: estudo bibliométrico do Banco de Teses da Capes - Silva, Rosemary Cristina da (2013)
The present research proposes to conduct a study on the field of Sociology of Education as presented in the theses and dissertations available in the CAPES Theses Database from the period from 1987 to 2011, based on bibliometric and scientometric approaches, in order to obtain a theoretical reflection on the field of Sociology of Education in Brazil that unfolds in the identification of: prime research topics in the field of Sociology of Education; aspects of sociological theory; the most influential authors and theoretical frameworks of reference in Sociology of Education. The data source was the CAPES Theses Database with contributions from BDTD/IBICT, the public domain and the digital libraries available for raw text access. The methodology was developed in four phases comprised of: construction of a theoretical reference; data collection in the CAPES Theses Database, BDTD, Public Domain Portal, description and categorization of survey data utilizing automated tools (the software programs Vantage Point and Excel) for the organization of the results obtained and subsequent analysis and interpretation. The chosen design consisted of two studies: Study 1: Bibliometric analysis of dissertations and theses in Sociology of Education with the aim of reporting the state of the art of the scientific production in this area; Study 2: Analysis of reference citations in light of theoretical approaches in Sociology of Education and Information Science, signifying the importance of combining different methodological perspectives to explore the same study object. In Study 1, we present the following results: the production of theses of dissertation occurred at some moments in an oscillating manner, but the increase was gradual throughout the studied period. The works at the Master s level predominated with 71% of the recovered records. With respect to distribution by institution and region, both indicators were found to be concentrated in the southeast region, that is, UFMG, PUC-SP and PUC-RIO were the most frequent institutions confirming the representativeness of this region in the national research. As to the administrative nature of the institutions, the Federal and Private institutions were predominant. The graduate programs that have most researched this topic indicate Education and Sociology given that Sociology of Education is the scientific field that has maintained historic relations with these areas. The most frequent theme is Education, followed by Sociology of Education. The Research Instigating Agencies that fund the most research studies are Capes and CNPq. The studies that did not receive financing correspond to 51% of the total, which indicates that these researchers are participating in the labor market. The female gender is present in 72% of the authorial credits in the dissertations and theses, confirming that women tend to predominate in the Human Sciences. Study 2 corresponds to the analysis of citations of books and chapters appearing in the theses and dissertations. The results show that in relation to the contemporaneousness of sources, the author shave relied on relatively recent literature, which can be explained based on the origin of Sociology of Education that, as a distinct field of Sociology, is relatively new; therefore, production in this area also tends to be new. As to book authorship, national and foreign authorial nuclei were identified. The most cited authors of the national nucleus are Maria Alice Nogueira, Paulo Freire, Florestan Fernandes and Demerval Saviani. The most cited in the foreign nucleus were Pierre Bourdieu, Émile Durkheim, Jean-Claude Passeron, Bernard Lahire and Michel Foucault. The most cited book title was A reproduction: elements for a teaching system theory , authored by Pierre Bourdieu and Jean-Claude Passeron. As to language indicators for the books and chapters, Portuguese predominated in the two sources. The editors of the books and chapters cited indicated Editor Voices as predominant in the most cited publications. In reference to authorship of book chapters, Pierre Bourdieu was the author of the majority of chapters cited. The indicator on authorship of books that integrate the chapters of books identified Maria Alice Nogueira as the most frequent author. The most mentioned chapter title was The conservative school: the inequalities facing the school and the culture, and is authored by Pierre Bourdieu; the books that integrate the book chapters presented the title Escritos de Educação (Writings from Education), organized by Maria Alice Nogueira and Afrânio Catani as the most cited. The data resulting from the three authorship indicators (authorship of books, authorship of chapters and authorship of books that integrate the chapters) constitute the research front found to be identified by 21 authors, 15 of whom are Brazilian and six foreign, that constitute the principle theoreticians and researchers that contribute to the theoretical underpinning that sustains the development of research studies in Sociology of Education in the production of theses and dissertations in Brazil. Through citation analysis, it was highlighted that the bourdieusian approaches are most often utilized as a theoretical referential in Sociology of Education theses and dissertations. The studies presented here in indicate the most influential authors and theoretical frameworks of reference utilized by the authors of theses and dissertations to support their research Sociology of Education and how they configure the national graduates cenario in Brazil.